2007
DOI: 10.1186/1471-2199-8-110
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor pathway inhibitor-2 was repressed by CpG hypermethylation through inhibition of KLF6 binding in highly invasive breast cancer cells

Abstract: Background: Tissue factor pathway inhibitor-2 (TFPI-2) is a matrix-associated Kunitz inhibitor that inhibits plasmin and trypsin-mediated activation of zymogen matrix metalloproteinases involved in tumor progression, invasion and metastasis. Here, we have investigated the mechanism of DNA methylation on the repression of TFPI-2 in breast cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…TFPI can also be synthesized and secreted into ECM by many other cells, including mesangial cells, smooth muscle cells, monocytes, fibroblasts, and cardiomyocytes [73,75,[78][79][80]. Potential binding sites for TFPI in the ECM are proteoglycans, as well as certain ECM proteins, such as collagen I, vitronectin, and laminin 5 [81].…”
Section: Tissue Factor Pathway Inhibitor (Tfpi)mentioning
confidence: 99%
“…TFPI can also be synthesized and secreted into ECM by many other cells, including mesangial cells, smooth muscle cells, monocytes, fibroblasts, and cardiomyocytes [73,75,[78][79][80]. Potential binding sites for TFPI in the ECM are proteoglycans, as well as certain ECM proteins, such as collagen I, vitronectin, and laminin 5 [81].…”
Section: Tissue Factor Pathway Inhibitor (Tfpi)mentioning
confidence: 99%
“…Given that transcription factors and coregulators can play opposing transcriptional roles in different physiological contexts (26,28,29,47), the opposing results concerning KLF6 or LCoR regulation of target genes in different cell lines is not surprising as the original studies that identified these genes as KLF6 targets were carried out in various cell lines from liver to vascular endothelial cells (40,41). Furthermore, the exact role of a transcriptional regulator depends on the additional interactions that occur on the promoter, which might differ in different tissues as was found for LSD1 whose role in transcriptional regulation is complex constituent-specific, and cell type-dependent (26).…”
Section: Discussionmentioning
confidence: 99%
“…7B). In addition to CDKN1A and CDH1, KLF6 has been shown to regulate the expression of the growth/ survival genes encoding activating transcription factor 3 (ATF3) and tissue factor pathway inhibitor 2 (TFPI2) (39,40), and genes encoding proteins associated with tumor cell migration matrix metalloproteinase-9 (MMP9) and urokinase plasminogen activator (uPA/PLAU) (41,42). LCoR ablation increased expression of the TFPI2 gene about 2-fold, whereas it slightly reduced ATF3 levels in PC-3 cells and had no significant effect on MMP9 or uPA expression (Fig.…”
Section: Lcor Corepresses Klf6 Target Genes Through Ctbp1-and Hdac-dementioning
confidence: 99%
“…Previous studies have demonstrated that silencing of TFPI-2 by either histone deacetylation (19) or promoter hypermethylation contributes to its inactivation and tumor progression in a variety of cancers including glioma (18), choricarcinoma (20), pancreatic carcinoma (17), lung carcinoma (21), breast cancer (22), melanoma (23) and hepatocarcinoma (24). In addition, the aberrant splicing form of TFPI-2 was detected during cancer progression (25), which represents an untranslated form providing another mechanism by which TFPI-2 is downregulated in tumor cells.…”
Section: Discussionmentioning
confidence: 99%